Dropouts in Swiss vocational education and the effect of training companies’ trainee selection methods - Forsblom, Lara [Verfasser]; Negrini, Lucio [Verfasser]; Gurtner, Jean-Luc [Verfasser]; Schumann, Stephan [Verfasser] (My University, 2016)
"In the Swiss vocational education system, which is often called a 'Dual System', trainees enter into an apprenticeship contract with a training company. On average, 25% of those contracts are terminated prematurely (PCT). This article examines the relationship between training companies' selection methods and PCTs. The investigation is based on a quantitative study with a cross-sectional design and on qualitative interviews. Trainers and operations managers (N = 335) of Swiss training companies for cooks and painters were surveyed. Half of the companies have been affected by a PCT in the past and the other half have not. The findings indicate that a certain amount of the explained variance between companies with and without reported PCTs can be explained by the companies' selection process. Companies that were affected by a PCT use a job interview and a company visit significantly less often in their selection process than companies without a PCT." (authors' abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); S 5.3 Personalentwicklung; T 3.4 Befragung; Berufsausbildung; Ausbildungsabbruch; Einflussfaktor; Personalauswahl; Auswahlverfahren; Maler; Koch; Betriebsbefragung; Schweiz